Implementation of the Jigsaw Learning Method for Maharah Qiro’ah Learning at MA As-Sholach, Kejeran Boyeman, Gondangwetan, Pasuruan - Mahmudah, Menik; Hanifansyah, Nur (Lughawiyah: Journal of Arabic Education and Linguistics, 2024)
This study examines the effectiveness of the Jigsaw Learning Method in enhancing student engagement, motivation, and comprehension in Maharah Qiro’ah (Arabic reading) instruction at Madrasah Aliyah (MA) As-Sholach. Traditional methods such as sorogan and direct translation have long been used in pesantren-based Arabic instruction. While these approaches emphasize teacher-centered learning and individual recitation, they often struggle to maintain student engagement and provide limited opportunities for collaborative and active learning. In contrast, the Jigsaw method fosters peer interaction, cooperative knowledge-sharing, and structured learning, potentially addressing the motivation and comprehension gaps found in traditional methods. This study employs a mixed-methods approach, combining quantitative data from structured pre-tests, post-tests, and Likert-scale questionnaires with qualitative insights from classroom observations, student interviews, and teacher feedback. The study involved 107 students from grades XI and XII, divided into Jigsaw learning groups for Maharah Qiro’ah lessons. Descriptive statistical analysis revealed that 93.5% of students found the method effective, with 88.8% reporting increased motivation and 82.2% demonstrating improved comprehension. However, challenges persisted in material suitability (76.6%) and vocabulary retention (76.6%), highlighting areas for instructional refinement. The qualitative findings further reinforce these results, indicating that while the Jigsaw method enhances engagement and peer collaboration, additional support mechanisms—such as pre-teaching vocabulary sessions, scaffolding techniques, and continuous teacher training—are needed to optimize learning outcomes. The findings suggest that integrating Jigsaw into pesantren-based education can improve Arabic reading comprehension while making lessons more engaging and student-centered. This research contributes to the growing body of literature on cooperative learning strategies in Islamic education and underscores the potential of structured collaborative methods to enhance Maharah Qiro’ah instruction.